Isotopic decay of urinary or plasma 3‐methylhistidine as a potential biomarker of pathologic skeletal muscle loss. Issue 1 (6th September 2013) - Sheffield-Moore, M.; Dillon, E. L.; Randolph, K. M.; Casperson, S. L.; White, G. R.; Jennings, K.; Rathmacher, J.; Schuette, S.; Janghorbani, M.; Urban, R. J.; Hoang, V.; Willis, M.; et al.
Abstract : Background: Skeletal muscle loss accompanying aging or cancer is associated with reduced physical function and predicts morbidity and mortality. 3‐Methylhistidine (3MH) has been proposed as a biomarker of myofibrillar proteolysis, which may contribute to skeletal muscle loss. Methods: We hypothesized that the terminal portion of the isotope decay curve following an oral dose of isotopically labeled 3MH can be measured non‐invasively from timed spot urine samples. We investigated the feasibility of this approach by determining isotope enrichment in spot urine samples and corresponding plasma samples and whether meat intake up to the time of dosing influences the isotope decay. Results: Isotope decay constants ( k ) were similar in plasma and urine, regardless of diet. Post hoc comparison of hourly sampling over 10 h with three samples distributed over 10 or fewer hours suggests that three distributed samples over 5–6 h of plasma or urine sampling yield decay constants similar to those obtained over 10 h of hourly sampling. Conclusion: The findings from this study suggest that an index of 3MH production can be obtained from an easily administered test involving oral administration of a stable isotope tracer of 3MH followed by three plasma or urine samples collected over 5–6 h the next day.